Nursing Students’ Experience and Perception towards Online Education during Covid-19 Pandemic in Nepal - Sah, Bimala Kumari; Silwal, Suvekshya; Adhikari, Bibhav; Pandey, Apsara; Gupta, Bipasha (International Journal of Silkroad Institute of Research and Training, 2024)
Background: The COVID-19 pandemic forced educational institutions worldwide to adapt swiftly. This study explored nursing students’ experiences and perceptions towards online education during the pandemic in Nepal. Method: Using a cross-sectional descriptive design, data were collected from 416 nursing students across the country using non probability convenient sampling technique via a google form questionnaire. Ethical approval was obtained from NHRC and for the data analysis, descriptive analysis was done by using appropriate statistical tools and SPSS version 20. Result: Key findings on online class experience, 93.5% participated in live online classes, 62.3% preferred a blend of subjective and objective evaluation methods and 58.9% favored pre- and post-classroom assignments. Similarly, regarding benefits of online education 25.0% strongly agreed that technical skills (email, internet, apps) improved, 53.1% recognized teachers’ facilitative role in student learning and 45.2% believed online classes reduced psychological stress. There were challenges on theory classes and clinical practicum where 38.8% acknowledged skill gaps for effective online teaching and 44.0% strongly agreed on curriculum redesign respectively. Conclusion: Online learning is crucial for a variety of reasons, including time savings and learning flexibility. Despite these, constrained technology infrastructures, connectivity issues and clinical practicum continued to be obstacles. Effective online education requires increased internet access, faculty and student digital training, and the support of regulatory authorities.